Proceedings of the 5th SEA-DR (South East Asia Development Research) International Conference 2017 (SEADRIC 2017) 2017
DOI: 10.2991/seadric-17.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

The Development of qChemtectiveq Game-Based Medium on Chemistry Learning

Abstract: Abstract-The purpose of this study was to develop "Chemtective" as a game-based learning medium which was valid, practical, and effective in improving students' interest and motivation in learning Chemistry. "Chemtective" is a computer game-based medium designed by collaborating "chemistry subject" and "detective stories". The method employed in this study was Research and Development (R & D). The validity of the medium was evaluated by three media experts. As many as 34 students of SMA Negeri 2 Banjarmasin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Wardani et al (2017) also developed a chemistry board game called alchemist board, which aimed at enhancing students' learning outcomes and critical thinking ability. Winarti et al (2017) developed computer game-based medium named "Chemtective" which was designed by collaborating the chemistry subject and detective stories to motivate and increase interest among students to learn chemistry.…”
Section: Educational Gamesmentioning
confidence: 99%
“…Wardani et al (2017) also developed a chemistry board game called alchemist board, which aimed at enhancing students' learning outcomes and critical thinking ability. Winarti et al (2017) developed computer game-based medium named "Chemtective" which was designed by collaborating the chemistry subject and detective stories to motivate and increase interest among students to learn chemistry.…”
Section: Educational Gamesmentioning
confidence: 99%
“…Integrating games in learning activities are not something new; some previous studies reported the development and implementation of gaming into learning activities. For example, [23] developed an Android game for learning colloids, Atiek et al [24] developed "chemtective" to learn chemistry through detective-problem solving. Wardani et al [25] have also developed a chemistry board game called the alchemist board, which aimed at enhancing students' learning outcomes and critical thinking ability.…”
Section: Educational Gamesmentioning
confidence: 99%